The Influence of Cross-Interest Economic Learning on Senior High School Students’ Learning Interest and Student Achievement - I Gusti Ayu Laksmi Trisnawati; Suparman Suparman; Fitra Hasri Rosandi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The 2013 curriculum provides opportunities for learners to develop their abilities, talents and interests more broadly and openly The purpose of this study is to analyze the influence of cross-interest economic learning on learning interest and Learning Achievement of Class XI MIA 1 SMA Negeri 3 Sumbawa Besar students. The type of research used by researchers is Quantitative research using experimental methods to measure relationships, the influence of variable differences. The results showed that there was an influence of learners across economic interests on learning interest and learning achievement from the results of the Anova column F test conducted with the spss version 22 application, a significant value for learning interest was obtained by 0.034 So it can be concluded that there is an influence of learning Cross economic interest on learning interest and learning achievement